'Stabilizer', a New Low‐Growing Siberian Wheatgrass Cultivar for Use on Semiarid Lands. Issue 1 (24th October 2012) - Jensen, K. B.; Bushman, B. S.; Waldron, B. L.; Robins, J. G.; Johnson, D. A.; Staub, J. E.
Abstract : The USDA‐ARS announces the public release of the cultivar 'Stabilizer' (Reg. No. CV‐33, PI 665034) Siberian wheatgrass [ Agropyron fragile (Roth) Candargy] as a low‐growing, rapid‐establishing revegetation grass for use on rangelands and roadsides and as a grass component in fire‐strip plantings in the Intermountain West, Great Basin, and northern Great Plains regions of the western United States. Selection emphasis in Stabilizer was for seedling establishment, persistence, seed production, pubescence, and reduced forage yield. During the establishment year, Stabilizer had similar numbers of seedlings per unit area, using a frequency grid, as did the cultivar 'Vavilov II' at Guernsey, WY, Dugway, UT, Beaver, UT, Fillmore, UT, and Malta, ID; and the cultivar 'Vavilov' at King Hill, ID and Spring City, UT. Stabilizer persisted as well as Vavilov II at Guernsey, WY, Fillmore, UT, and Beaver, UT but was significantly more persistent than Vavilov II at Malta, ID. Stabilizer had significantly less dry matter yield (0.25 kg plot −1 ) at Beaver, UT than Vavilov II (0.53 kg plot −1 ) and Vavilov (0.60 kg plot −1 ). Stabilizer was genetically distinct and unique with respect to the other available Siberian wheatgrass varieties.